Impact of comprehensive optical diagnosis training using Workgroup serrAted polypS and Polyposis classification on detection of adenoma and sessile serrated lesion. Issue 1 (12th July 2021) - Lee, Jooyoung; Bae, Jung Ho; Chung, Su Jin; Kang, Hae Yeon; Kang, Seung Joo; Kwak, Min‐Sun; Seo, Ji Yeon; Song, Ji Hyun; Yang, Sun Young; Yang, Jong In; Lim, Seon Hee; Yim, Jeong Yoon; et al.
Abstract : Objectives: Many interventions have been attempted to improve adenoma detection rate (ADR) and sessile serrated lesion detection rate (SDR), and one of these interventions is educational training to recognize polyp characteristics. This study aimed to investigate the change in polyp detection rates of endoscopists before and after comprehensive training through the Gangnam‐Real Time Optical Diagnosis (Gangnam‐READI) program. Methods: Fifteen gastroenterologists participated in a 1‐year comprehensive training program that consisted of ex vivo and in vivo training that encompasses knowledge and skills in endoscopic characterization of colonic polyps using the Workgroup serrAted polypS and Polyposis (WASP) classification. We evaluated the impact of the training program by comparing the overall and individual ADR and SDR 6 months before and after the training. Results: Overall, 18, 280 polyps (9337 adenomas and 855 sessile serrated lesion) were collected. The optical diagnosis training had no significant impact on the difference in ADR after training compared to before training (47.7% vs. 46.5%, P = 0.608). A tendency for a decrease in ADR variance was noted among the endoscopists after training (74.9 vs. 32.7, P = 0.121). The overall pre‐training period SDR was 4.5% and showed a statistically significant increase to 5.6%, 8.0%, and 7.1% in the first and second half of the training period, and post‐training period, respectively ( P = 0.003). The optical diagnosis training did not decrease variance in SDR (8.9 vs. 8.8, P = 0.985). Conclusion: Comprehensive optical diagnosis training with WASP classification has a significant impact on increasing the overall SDR of expert endoscopists.